Inkulturasi Dan Pemaknaan Misa Imlek Dalam Gereja Katolik: (Tinjauan Fenomenologi Armada Riyanto) - Fransesco Agnes Ranubaya; Nikodemus; Yohanes Endi (Jayapangus Press, 2023)
The focus of this research is the Inculturation and meaning of Chinese New Year in the Catholic Church. The population of Indonesia consists of various tribes, religions and races. This shows the heterogeneity in Indonesia. Among the ethnic groups in Indonesia is the Chinese. In Chinese culture, the author discusses the meaning of thanksgiving for Chinese New Year celebrations. Thanksgiving is contained in the celebrations such as: the meaning of chinese new year mass in liturgy, the meaning of eating together, the meaning of chinese new year in the catholic church, and the church gives space; chinese new year inculturation. New year celebrations in China are symbolic rituals that adherents believe can bring blessings and happiness in the coming year. The purpose of the study was to determine the location of the inculturation of the celebration of Chinese New Year mass in the Catholic Church, understanding the meaning of inculturation and understanding of the celebration of Chinese New Year in the Eucharist. The findings in this research are contained in a framework that describes the reality of the meaning of the Inculturation of Chinese New Year Mass in the Catholic Church as a celebration of gratitude. The results of this study form the basis for the implementation of the Catholic Incutoration today. The author hopes to help, add human insight to Chinese New Year culture. The way of viewing and responding to an event spiritually has long existed and is part of the cultural tradition in Asia. So that Inculturation gives life to the Church filling and edifying with the light of faith, of Christ in the unity of Church tradition. This research is very relevant to today's situation, especially for the younger generation to get to know the various cultures that are integrated into the Church tradition as a unique and meaningful unity of faith.